Fiber Optic Sensors for Structural and Geotechnical Monitoring - Caponero, Michele Arturo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The use of sensors based on fibre optic technology allows a broad range of applications in the fields of structural and geotechnical monitoring, which can effectively improve the maintenance of infrastructures and the safety of communities. Thanks to its valuable features, such as distributed monitoring, the easiness and endurance of cabling, long term stability, reliable responses in both static and dynamic regimes and fibre optic technology, innovative and efficient solutions to quite difficult monitoring problems have already been provided. The increasing worldwide attention to infrastructures and communities with resilience capabilities against natural disasters has opened up new and challenging perspectives of applications to the use of fibre optic technology for structural and geotechnical monitoring. This book collects contributions in the development and application of monitoring solutions, based on fibre optic technology for structural and geotechnical engineering works and issues. In the book preface, the content of the contributions is reviewed, pointing out the relevance of the work, with respect to the advance and spreading of fibre optic technology for monitoring applications. All contributions provide a comprehensive discussion and report a rich bibliography on the current trends and issues relative to the theme of the work presented.